2017
DOI: 10.1002/cssc.201701456
|View full text |Cite
|
Sign up to set email alerts
|

3 D Porous Nickel–Cobalt Nitrides Supported on Nickel Foam as Efficient Electrocatalysts for Overall Water Splitting

Abstract: Exploring highly efficient and durable bifunctional electrocatalysts from earth-abundant low-cost transition metals is central to obtaining clean hydrogen energy through large-scale electrolytic water splitting. Porous nickel-cobalt nitride nanosheets on macroporous Ni foam (NF) are synthesized through facile electrodeposition followed by a one-step annealing process in a NH atmosphere. The transformation from a metal hydroxide into a metal nitride could efficiently enhance the electrocatalytic performance for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
105
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(114 citation statements)
references
References 44 publications
5
105
1
Order By: Relevance
“…The OER performances of the present NFN-MOF/NF electrode are compared with those of recently reported stateof-the-art NF-based OER electrocatalysts [28,[42][43][44][46][47][48][49][50][51][52][53][54][55][56][57] in terms of catalyst loading on NF, η 10 , η at higher current densities if available, Tafel slope, and stability in Table S1 (Supporting Information). Evidently, the present NFN-MOF/NF electrode competes favorably.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OER performances of the present NFN-MOF/NF electrode are compared with those of recently reported stateof-the-art NF-based OER electrocatalysts [28,[42][43][44][46][47][48][49][50][51][52][53][54][55][56][57] in terms of catalyst loading on NF, η 10 , η at higher current densities if available, Tafel slope, and stability in Table S1 (Supporting Information). Evidently, the present NFN-MOF/NF electrode competes favorably.…”
Section: Resultsmentioning
confidence: 99%
“…It is better than the electrode having the bimetallic MOF but without the NH 2 group, MIL-88B(Fe 2 Ni)-MOF/ NF, implying the importance of the amino group in boosting the HER performance. It also stands out among the recently reported top transitionmetal-based bifunctional electrocatalysts on NF for overall water splitting, including NiFe/NiCo 2 O 4 /NF (1.67 V), [42] NiCo 2 S 4 / NF (1.63 V), [43] annealed Co-Ni-B@NF (1.72 V), [44] FeNi 3 N/NF (1.62 V), [46] NiSe/NF (1.63 V), [48] NiCo 2 N-NF (1.70 V), [54] and Co 1 Mn 1 CH/NF (1.68 V) [55] (Table S6, Supporting Information). The metal ions (Fe 3+ and Ni 2+ ) of the NFN-MOF may be partially reduced to its metallic state forming M/MO 6 clusters.…”
Section: Resultsmentioning
confidence: 99%
“…Notable reports here include work that began from research on the impact of the Co/N ratio in cobalt nitride catalysts. Other TMNs, such as NiCo 2 N( 180 mV overpotential,1 .32 Vo nset potential, 55 mV Ta fel slope), [53] NiMoN/CF (210 mV overpotential, 1.32 Vo nset potential, 55 mV Tafel slope), [54] and Ni 3 MnN (320 mV overpotential, 1.60 Vo nsetp otential, 64 mV Ta fel slope) [55] have also been studied for the OER. For example, Sun et al reported that it "further improved the OER activity in both neutral and alkaline solutions, with high stabilityi n3 0000 cycles".…”
Section: Transition Metal Nitride Oer Electrocatalystsmentioning
confidence: 99%
“…Wang et al [53] also synthesized the Ni-based ternary nitride 3D NiCo 2 Nb ye lectrodeposition on nickel foam (NF) support (Table 3). In addition, the fabrication of 3D interrelated macroporous NF with high surface area exposed extra active sites, which facilitates charge transfer and gas diffusion (H 2 ).…”
Section: Nickel-cobalt Nitrideo Er Electrocatalystsmentioning
confidence: 99%
“…However, the scarcity of noble metals limits the widespread application . Therefore, tremendous efforts have been made to design earth‐abundant electrocatalysts with high activity and stability, such as transition metal chalcogenides, carbides, phosphides, and nitrides for HER, and cobalt‐phosphate, perovskite oxides, and 3d transition metal–based (oxy)hydroxides for OER. Considering the compatibility of the electrocatalysts in the same electrolyte for both HER and OER simultaneously, exploring highly efficient and stable bifunctional electrocatalysts toward overall water splitting is highly desirable.…”
Section: Introductionmentioning
confidence: 99%